Extragingival pyogenic granuloma histologically mimicking capillary hemangioma - Dahiya, Ritu (J Indian Soc Periodontol, 2014)
Pyogenic granuloma is a tumor-like proliferation to a non-specific infection. The tumor-like growth is considered to be non-neoplastic in nature and presents in various clinical and histological forms in the oral cavity. Hemangiomas are benign vascular anomalies characterized by benign proliferation of blood vessels. The aim of this article is to drive attention toward the uncommon location of capillary hemangioma on the palate. In spite of their benign nature, intraoral capillary hemangiomas are always clinically important to be diagnosed well in time and suitably managed. The lesion in the present case although clinically diagnosed as pyogenic granuloma gave a histological picture of capillary hemangioma when surgically excised.